Environmental sustainability and nutritional quality: addressing global food and nutrition insecurity in a post-pandemic world - Cao, Youshen; Li, Yaonan; Liu, Tianqi; Ye, Zixuan; Lee, Sangho; Geng, Shengkai; Haou, Cai (Frontiers in Nutrition, 2025)
BackgroundThis study examines the interrelated issues of food and nutrition insecurity in the post-COVID-19 period, emphasizing the effects of environmental preservation, environmental degradation, and global financial disturbances. Over the last decade, the world has faced unprecedented challenges in food production and delivery, including resource scarcity, biodiversity loss, and substantial price increases. Between 2019 and 2023, over 120 million individuals, representing almost 21% of the global population, experienced food insecurity, underscoring the need to address these challenges.ObjectivesThe research utilizes the IMPACT model, augmented with climate projections, agricultural experiments, water cycle evaluations, and global agricultural balance models, to assess the global food supply.MethodImplies IMPACT model.ResultsThe results underscore the need for environmentally sound farming methods and climate resilience to ensure food security in a rapidly changing global landscape.ConclusionThis study provides thorough qualitative and quantitative perspectives on the intricacies of worldwide nutrition and food systems by examining net accessible calories supply, hunger distribution, micronutrients distribution, and sink calories.